2006
DOI: 10.1088/0957-4484/17/5/043
|View full text |Cite
|
Sign up to set email alerts
|

The influence of protective coatings on the magnetic properties of acicular iron nanoparticles

Abstract: Core–shell acicular nanoparticles of ∼90 nm length and ∼5 axial ratio consisting of an iron core coated with an oxidized layer of different composition have been obtained by thermal reduction with hydrogen of coated goethite precursors. Uniform goethite particles were prepared by oxidation in air of FeSO4 solutions previously precipitated with Na2CO3. Al or Y oxide layers were deposited on the goethite particle surface by heterocoagulation. The efficiencies of both compounds as protecting agents for preventin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Finally, the XPS spectra also showed the bands at 156.7 and 73.6 eV (data not shown) associated with Y(III) and Al(III) cations, respectively [24], whose proportion in the particle outer layers (30 and 18 mol%, respectively, as determined by XPS) was higher than that in the overall solid determined by XRF (5 mol% in both cases). These results confirmed that Y(III) and Al(III) cations were located on the particle's surface during reduction, thus preventing interparticle sintering [13,17]. These phases were not detected by XRD due to their amorphous character and low proportion.…”
Section: Co Xrf (Mol%)supporting
confidence: 61%
See 2 more Smart Citations
“…Finally, the XPS spectra also showed the bands at 156.7 and 73.6 eV (data not shown) associated with Y(III) and Al(III) cations, respectively [24], whose proportion in the particle outer layers (30 and 18 mol%, respectively, as determined by XPS) was higher than that in the overall solid determined by XRF (5 mol% in both cases). These results confirmed that Y(III) and Al(III) cations were located on the particle's surface during reduction, thus preventing interparticle sintering [13,17]. These phases were not detected by XRD due to their amorphous character and low proportion.…”
Section: Co Xrf (Mol%)supporting
confidence: 61%
“…Essentially, it consists of the preparation of Co-doped goethite acicular nanoparticles (GCo 10 ) and their further coating with Co(OH) 2 to increase their Co content. At the same time, they were also coated with yttrium oxide (Y/(Fe + Co + Y) atomic ratio = 5%), which has been shown to be the optimum preventing sintering agent [15,17]. This goethite precursor was first dehydroxylated yielding haematite (HCo 10 ), which was finally reduced to obtain the Fe-Co alloys by using three different protocols, aiming to increase the amount and to obtain a more homogeneous distribution of alloyed Co in the final particles.…”
Section: Preparation Of Fe-co Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important because many types of highmagnetism nanoparticles easily oxidize in air, diminishing their magnetism. [28,29] A protective layer that resists oxidation can significantly improve the applicability of these materials. Lastly , composite nanoparticles usually possess more than one type of surface, enabling them to be tethered easily, with multiple functionalities and minimal cross-species interference.…”
Section: Introductionmentioning
confidence: 99%
“…However, Fe particles in nano form have a high affinity for oxygen. Despite the reduction of their total magnetic moment, when dispersed in non-magnetic matrix or coating, several studies have been conducted to encapsulate these particles in silica [1,3], alumina [4], yittria [5,6], gold [7], carbon [8], boron nitride [9], and Fe 3 O 4 [10,11] in order to improve their stability, electrical and magnetic properties. Fe-silica nanocomposites are of particular interest because they have higher resistivity and this combined with the good magnetic properties of metallic Fe, makes them a good candidate for dielectric applications and could possibly be a good replacement material for ferrites.…”
Section: Introductionmentioning
confidence: 99%